2006
DOI: 10.1159/000096520
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Study of Endoscopic Endonasal Conjunctivodacryocystorhinostomy with Jones Tube Placement

Abstract: Purpose: To evaluate the efficacy of endoscopic endonasal primary conjunctivodacryocystorhinostomy (CDCR) and revision CDCR after primary CDCR. Methods: Twenty-four patients who had undergone endoscopic endonasal CDCR with a Jones tube and who were followed up for over 6 months at our hospital were reviewed retrospectively. Our analysis included success rate, operation times, and causes of failure. Results: The indications for revision CDCR were Jones tube prolapse and inadequate tube length. The initial succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 13 publications
1
32
0
1
Order By: Relevance
“…While this study was limited by a relatively small sample size and varying follow-up duration, it demonstrated the advantages of endonasal CDCR. In a previous report from 2007, the primary success rate of endonasal CDCR was 78.6% at 6 months postoperative and the mean operation time was 24 min (Park et al, 2007). In the present study, the primary success rate was 87.9% and the mean operation time was 26 min.…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…While this study was limited by a relatively small sample size and varying follow-up duration, it demonstrated the advantages of endonasal CDCR. In a previous report from 2007, the primary success rate of endonasal CDCR was 78.6% at 6 months postoperative and the mean operation time was 24 min (Park et al, 2007). In the present study, the primary success rate was 87.9% and the mean operation time was 26 min.…”
Section: Discussionsupporting
confidence: 63%
“…Some reports have demonstrated the effectiveness of endonasal CDCR. Boboridis and Downes reported a 75% success rate for 16 cases (Boboridis and Downes, 2005); Park et al reported a 78.6% success rate for 14 cases (Park et al, 2007) and Trotter and Mayer reported a 100% success rate for 7 cases (Trotter and Meyer, 2000). To the best of our knowledge, there is only one report that has compared the two techniques, which demonstrated some advantages of endonasal CDCR (Trotter and Meyer, 2000).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations